Communication Research Trends in Virtual Project Team: Bibliometric Analysis - Susanto Susanto; Tejo Ismoyo; Sunter Candra Yana; Rapiadi Rapiadi; Wistina Seneru (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The research on communication within the virtual project team has been conducted, and it is essential to identify which parts of the study have been explored and need more attention. It is necessary to analyze which countries and authors contributed the most and the types of publications used the most on communication in virtual project teams. Although there are many reviews of the literature on project communication issues and the different aspects of virtual teams, none of them are specifically dedicated to the topic of communication in virtual project teams. This article aims to identify scientific outputs in communication in virtual project teams from 2001 to 2020 and analyze their volume and geographic distribution. A bibliometric analysis approach was applied to this study to answer research questions regarding the number of publications in the research period, the most contributing countries and the most prolific authors, the types of publications applied, and the research topics discussed in the literature studied. Three search engine databases, Scopus, Web of Science, and Google Scholar, are used to find the publications of communication in the virtual project team and answer research questions. The results of the bibliometric analysis explain that the most frequently discussed topics concern the methods and tools for communication in virtual teams, while issues on communication-related to trust or leadership are the least explored areas.